Respiratory gating of endoscopic OCT images of the upper airway - McLaughlin, R.; Armstrong, J.; Becker, S.; Walsh, J.; Kirkness, J.; Jain, A.; Leigh, M.; Williamson, J.; Hillman, D.; Eastwood, Peter; Sampson, D. (2008)
Anatomical optical coherence tomography (aOCT) is an endoscopic imaging modality that can be used to quantify size and shape of the upper airway. We report the application of respiratory gating to aOCT images. Our results show that respiratory gating can reduce motion artefact in upper airway images. Using an error metric based on distance to the dominant reflection in each A-scan, we found notable improvements when the breath cycle was partitioned into approximately four gates, but only minor improvements as the number of gates was further increased.